PEMBELAJARAN MATEMATIKA YANG BERMUATAN NILAI ISLAM - Salafudin (JURNAL PENELITIAN, 2015)
This study aims to determine the current model of mathematics instructional in elementary school and the development of mathematics instructional model of Islamic values in elementary school. This study used developmental research approach. The experiment was conducted in SDIT Ulul Albab Pekalongan by taking Class V as research subjects. Using observation and interviews, this study resulted in: (1) strategies, methods, and techniques, as well as textbooks selected in the learning process are teachers' board decision based on the curriculum used in SDIT Ulul Albab; (2) the strategy employed using active learning, (3) Lecture, question and answer, drill / exercise, game, and song are current mathematics instructional model ; (4) the current model has not been effective in providing insight and character formation of students; (5) The materials and exercises are lack of Islamic values and incomplete; and (6) the limited addition of the peculiarities of Islamic Schools Integrated in mathematics.